Ethephon Reduces Maize Nitrogen Uptake but Improves Nitrogen Utilization in Zea mays L. - Zhang, Yushi; Wang, Yubin; Liu, Churong; Ye, Delian; Ren, Danyang; Li, Zhaohu; Zhang, Mingcai (Frontiers in Plant Science, 2022)
Increasing use of plant density or/and nitrogen (N) application has been introduced to maize production in the past few decades. However, excessive planting density or/and use of fertilizer may cause reduced N use efficiency (NUE) and increased lodging risks. Ethephon application improves maize lodging resistance and has been an essential measure in maize intensive production system associated with high plant density and N input in China. Limited information is available about the effect of ethephon on maize N use and the response to plant density under different N rates in the field. A three-year field study was conducted with two ethephon applications (0 and 90 g ha-1), four N application rates (0, 75, 150, and 225 kg N ha-1), and two plant densities (6.75 plants m-2 and 7.5 plants m-2) to evaluate the effects of ethephon on maize NUE indices (N agronomic efficiency, NAE; N recovery efficiency, NRE; N uptake efficiency, NUpE; N utilization efficiency, NUtE; partial factor productivity of N, PFPN), biomass, N concentration, grain yield and N uptake and translocation properties. The results suggest that the application of ethephon decreased the grain yield by 1.83-5.74% due to the decrease of grain numbers and grain weight during the three experimental seasons. Meanwhile, lower biomass, NO3- and NH4+ fluxes in xylem bleeding sap and total N uptake were observed under ethephon treatments. These resulted in lower NAE and NUpE under the ethephon treatment at a corresponding N application rate and plant density. The ethephon treatment had no significant effects on the N concentration in grains, and it decreased the N concentration in stover at the harvesting stage, while increased the plant N concentration at the silking stage. Consequently, post-silking N remobilization was significantly increased by 14.10-32.64 % under the ethephon treatment during the experimental periods. Meanwhile, NUtE significantly increased by ethephon.